1977
DOI: 10.1111/j.1445-5994.1977.tb04678.x
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Clonidine by Intramuscular Injection in the Treatment of Hypertension*

Abstract: Clonidine (Catapres) administered intramuscularly in a dose of 150 microng produced a satisfactory reduction in blood pressure in 13 of 16 hypertensive patients. Its effect occurred within five minutes, was maximal at 75 minutes and persisted for five hours. In six patients who received two doses (150 microng and 300 microng), the response was shown to be dose-related. No serious side effects were noted. Intramuscular administration of clonidine thus appears to be safe and effective. It has a place in the mana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1978
1978
1999
1999

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 4 publications
1
1
0
Order By: Relevance
“…In the study of Graham et al (1977), the dose-related nature of intramuscularly administered clonidine was inferred from the finding of a greater response to a 0.3 mg dose than to 0.15 mg, and in support of this premise, these doses (approximately 0.002-0.004 mg/kg) correspond to the lower end of the linear dose-response relationship obtained in the present study.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…In the study of Graham et al (1977), the dose-related nature of intramuscularly administered clonidine was inferred from the finding of a greater response to a 0.3 mg dose than to 0.15 mg, and in support of this premise, these doses (approximately 0.002-0.004 mg/kg) correspond to the lower end of the linear dose-response relationship obtained in the present study.…”
Section: Discussionsupporting
confidence: 59%
“…From a recent study in which clonidine, 150 pg intramuscularly, produced a satisfactory antihypertensive response in thirteen out of sixteen patients (Graham, Gain & Stokes, 1977), it was concluded that intramuscular administration of clonidine was an acceptable alternative to its intravenous use in the management of uncontrolled hypertension which was not amenable to oral therapy. However, the study was not a controlled one and its design did not permit the occurrence of initial pressor effects to be excluded.…”
Section: Introductionmentioning
confidence: 98%